Prevalence of guttae in the graft following corneal transplantation. Issue 12 (8th May 2015) - Nahum, Yoav; Canton, Veronica; Ponzin, Diego; Busin, Massimo
Abstract : Aim: To evaluate the prevalence of guttae in donor grafts following corneal transplantation and to examine the possible effect of guttae on postoperative results. Methods: Retrospective cohort study. We reviewed the medical records of all keratoplasties performed at the Villa Serena-Villa Igea private hospitals (Forlì, Italy) between January 2005 and July 2014. Endothelial specular microscopy images were examined to identify the presence of guttae. Donor's age, patient's age, indication for surgery, surgical procedure, postoperative visual acuity, and endothelial cell density were also noted. Results: A total of 11 068 postoperative specular microscopy pictures were available for 1116 of 2332 eyes (47.9%) that underwent keratoplasty at our institution. Guttae were identified in 42 of 946 eyes (4.44%) following penetrating or endothelial keratoplasty, and in 3 of 170 eyes (1.76%) following anterior lamellar keratoplasty. Twenty-seven of these photos demonstrated a few isolated scattered guttae, nine showed widespread guttae with small patches, and nine demonstrated large patches of guttae. Last documented best spectacle-corrected visual acuity did not differ between patients with or without guttae (logarithm of the minimum angle of resolution (logMAR) 0.22±0.24 (approximately 20/32) vs 0.29±0.45 (approximately 20/40), p=0.25) nor did the groups differ in their 24-month postoperative endothelial cell density (1633±427 vs 1555±454 cells/mm 2, p=0.56). No graft with postoperative guttae failed during the follow-up period of this study. Conclusions: Guttae can be found in approximately 4% of post-keratoplasty grafts. At least for the initial two postoperative years, they do not negatively affect vision, endothelial cell density or graft survival.